ASSESSMENT OF THE STATUS OF THE HEALTH OF WORKERS ROLLING PRODUCTION FOR THE INCIDENCE - Тулеген Нургалиевич Хамитов (Медицина в Кузбассе, 2018)
Objective. The health condition of workers of rolling production for the incidence of workers rolling production of JSC «ArcelorMittal».